Endometriotic Peritoneal Fluid Promotes Myofibroblast Differentiation of Endometrial Mesenchymal Stem Cells - Zhenzhen Zhang; Luxuan Suo; Yabing Chen; Li Zhu; Guiping Wan; Xiaodong Han (Stem Cells International)
During the development of endometriosis, the presence of fibrotic tissues in and surrounding endometriotic lesions may lead to subsequent adhesion, anatomic distortion, and chronic pain. Therefore, studies aimed at clarifying the underlying mechanisms of fibrogenesis in endometriosis could potentially provide a novel strategy for effective treatment. Mesenchymal stem cells (MSCs) play a key role in fibrotic diseases by differentiating into myofibroblasts in appropriate microenvironment. In this study, we collected endometrial and endometriotic tissues from patients with endometriosis (n=32) and control patients without endometriosis (n=20) to compare the expression of fibrotic proteins and investigate the effect of endometriotic peritoneal fluid (PF) on myofibroblast differentiation of endometrial MSCs. We found that the expression of fibrotic proteins, including alpha-smooth muscle actin (α-SMA), type I collagen (collagen I), connective tissue growth factor (CTGF), and fibronectin, and the extent of fibrosis extremely enhanced in ectopic endometria compared with eutopic endometria from the same patients with endometriosis and normal endometria from patients without endometriosis. We next isolated and identified endometrial MSCs and found that treatment with endometriotic PF strongly induced endometrial MSCs to differentiate into myofibroblasts concomitant with the activation of Smad2/3. Moreover, ectopic endometrial MSCs expressed elevated collagen I, α-SMA, fibronectin, and CTGF. Sushi domain containing-2 (SUSD2), a marker of endometrial MSCs, and α-SMA, a well-recognized marker for myofibroblasts, colocalized extensively in ectopic endometria while seldom in normal and eutopic endometria. These findings suggest that ectopic endometrial MSCs are probably more susceptible to myofibroblast differentiation because of the long-term influence of endometriotic PF. All together, we report for the first time that endometriotic PF promotes myofibroblast differentiation of endometrial MSCs. This understanding will greatly improve our understanding of the pathophysiology of endometriosis and help design better therapeutics.